An Evaluation of the Autopsy Cases of Carbon monoxide Poisoning in Trabzon Between 2009-2016 - Ketenci, Hüseyin Çetin; Karadeniz, Hülya; Boz, Halil; Beyhun, Nazım Ercüment (The Bulletin of Legal Medicine, 2018)
Objective: Carbon monoxide related deaths, which are generally preventable accidents, and more common when compared with other toxic substance consumption, arouse public attention in our country.Materials and Methods: In this study, the aim is to investigate different features of carbon monoxide poisoning related deaths autopsied in Trabzon in 8-year period of time and demonstrate medico-legal aspects of this issue.Results: Our study consists of all deaths due to carbon monoxide poisoning and autopsied by Trabzon Morgue Department of the Council of Forensic Medicine of Turkey between 2009 and 2016. Records of a total of 7133 criminal cases who were autopsied between these years were examined and 215 cases who died due to CO poisoning were evaluated for age, sex, the month of the event occurred, origin, death time, CO source and carboxyhemoglobin (COHb) values. 215 criminal cases were constituting 3.01% of 7133 criminal cases who were autopsied within 8 years in Trabzon. 91 of the cases were (42.3%) female and 124 were (57.7%) male and the male/female case ratio was 1.4. Mean age of the cases was 48.8±27.1years. 24.1% of deaths occurred in January 74% at home. CO source was found to be charcoal in 55.3% of cases. Mean COHb level detected in cases was 54.9±17.6%.Conclusion: Carbon monoxide poisoning is an important social problem in our country as in many developing countries. It is concluded that with their medicolegal experiences and suggestions, forensic medicine specialists can play an important role to manage carbon monoxide poisonings which are mainly...
Keywords: carbon monoxide; autopsy; poisoning; toxicology